Message from the Chief Editor: JTET December 2017 - Editor, Chief (Journal of Technical Education and Training, 2017)
Welcome to the 2017 December issue of the Journal of Technical Education and Training. In this issue we present eight papers from Indonesia, Malaysia, Nigeria, and Thailand with diverse perspectives on TVET practices and concerns. The papers highlight four broad themes namely, employability skills, vocational pedagogy, education for sustainability and entrepreneurship. The first two papers are concerned with identifying skills set to meet industry needs. The first paper from Thailand by Siddoo, Sawattawee, Janchai and Yodmongkol highlights the current concern on competency gaps that are observed among IT graduates as seen from the perspective of Thailand’s industries. To wrap up on the employability skills theme, the second paper by Mahfud, Jati, and Mulyani demonstrated the viability of using competency mapping as a tool for identifying industry soft skills needs giving an example from its application in the Indonesian hospitality sector. Acquisition of the desired competencies and skills however, are only possible through appropriate use of pedagogy or vocational pedagogy as it is preferably known in the TVET sector. Thus, the concept of vocational pedagogy is gaining greater prominence with increased needs to provide effective and efficient TVET provisions. In the third paper by Md Yunos et al., they discuss the efforts made to identify prevalant pedagogical practices among vocational teachers in Malaysia and Indonesia, while in the fourth paper, Nurlaela, Romadhoni, Widodo and Ana discuss how problem solving skills - an important skill of the 21st century – can be developed through appropriate use of pedagogical tools with successful examples from the home economics studies. Besides the home economics, sustainable education is another area where good practices are emerging as discussed in the fifth paper by Oviawe, Uwameiye, and Uddin, who share examples of practices from Nigeria. In Malaysia, efforts towards sustainability are enhanced with the transformation of technical schools into vocational colleges as discussed in the sixth paper by Manap, Hassan and Syahrom who share their findings on the issues and challenges facing those involved in the transformation journey. Recent development in recognizing entrepreneurial skills as generic skill has led to greater efforts to understand it. In the seventh paper, Inuwa and Ibrahim Mohammed investigate the role of psychological factors in shaping individuals’ entrepreneurial intention in Nigeria. Another similar focus of study was also conducted by Entika, Mohammad, Jabor and Osman in Malaysia who identified the necesary skills set for entrepreneurship in the engineering practice while calling for greater efforts to undertsand the contribution of contextual factors in defining the characterstics of entrepreneural skills set. We sincerely hope that the information shared are of benefit to our readers. Last but not least, we would like to thank all contributors and reviewers who make the timely publication of the current issue possible. We look forward to receiving more contributions from researchers and practitioners for our future issues. Happy Holidays and Happy New Year for the upcoming seasons. Professor Dr. Maizam Alias Chief Editor